Gambogic acid: Multi-gram scale isolation, stereochemical erosion toward epi-gambogic acid and biological profile - Arevalo, Gary E.; Frank, Michelle K.; Decker, Katelin S.; Theodoraki, Maria A.; Theodorakis, Emmanuel A. (Frontiers in Natural Products, 2023)
Introduction: Extracted from gamboge resin, gambogic acid (GBA) is a natural product that displays a complex caged xanthone structure and exhibits promising antitumor properties. However, efforts to advance this compound to clinical applications have been thwarted by its limited availability that in turn, restricts its pharmacological optimization. Methods: We report here an efficient method that allows multigram scale isolation of GBA in greater than 97% diastereomeric purity from various sources of commercially available gamboge. The overall process includes: (a) isolation of organic components from the resin; (b) separation of GBA from the organic components via crystallization as its pyridinium salt; and (c) acidification of the salt to isolate the free GBA. Results and Discussion: We found that GBA is susceptible to epimerization at the C2 center that produces epi-gambogic acid (epi-GBA), a common contaminant of all commercial sources of this compound. Mechanistic studies indicate that this epimerization proceeds via an ortho-quinone methide intermediate. Although the observed stereochemical erosion accounts for the chemical fragility of GBA, it does not significantly affect its biological activity especially as it relates to cancer cell cytotoxicity. Specifically, we measured similar levels of cytotoxicity for either pure GBA or an equilibrated mixture of GBA/ epi-GBA in MBA-MB-231 cells with IC50 values at submicromolar concentration and induction of apoptosis after 12 hours of incubation. The results validate the pharmacological promise of gambogic acid and, combined with the multigram-scale isolation, should enable drug design and development studies.